Factors that influence the increase of Eucheuma cottonii Seaweed farmers’ income in Bantaeng, South Sulawesi - Rusni Fitri Y. Rusman; Ikawati Karim; Ariady Arsal (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Seaweed is one of the marine production that authentically potential to be increased its production in quantity and quality. In economic side, it is not only for country’s foreign exchange earnings but also for a source of income to the seaweed farmers. The aims of research were to elaborate the influencing use of seed, number of labor, and farming experience on seaweed production in Bantaeng Regency and to analyze the influencing production to the farmers’ income. The research was conducted in Bantaeng Regency and the data were obtained through observation and structured interview. The samples were selected purposively consisting of 94 seaweed farmers using cobb-douglas and simple linear regression analysis. The results of the research indicated that; (a) regression coefficient variable in use of seed had influence to the increased of seaweed production but regression coefficient variable number of labor didn’t have to influence to increased seaweed production. For regression coefficient variable of farming experience also had influence to the increased seaweed production.Cobb-Douglas analysis indicated that production function in factors use of seed, number of labor and farming experience had significantly affected to the seaweed production. In simple linear regression analysis, regression coefficient of seaweed production variable explained if seaweed production increases, farmers’ income would be increase too. Keywords : Seaweed, Cobb-Douglas, Production, Farmers’ Income.